2018
DOI: 10.1111/jopy.12380
|View full text |Cite
|
Sign up to set email alerts
|

Becoming who you are: An integrative review of self‐determination theory and personality systems interactions theory

Abstract: One of the enduring missions of personality science is to unravel what it takes to become a fully functioning person. In the present article, the authors address this matter from the perspectives of self-determination theory (SDT) and personality systems interactions (PSI) theory. SDT (a) is rooted in humanistic psychology; (b) has emphasized a first-person perspective on motivation and personality; (c) posits that the person, supported by the social environment, naturally moves toward growth through the satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 121 publications
3
63
1
1
Order By: Relevance
“…We begin with the piece by Koole et al () in part because SDT has had a rich history of connecting with scholars in PSI (e.g., Ryan, Kuhl, & Deci, ), and more generally, the longer tradition of volitional psychologies from Germany (e.g., Heckhausen, ; Krapp & Ryan, ). Recently, Ryan (), in a volume honoring PSI founder Julius Kuhl, suggested that SDT and PSI are “sibling theories,” both being organismic in their meta‐theoretical assumptions, and overlapping in their interests in autonomy and control in human behavior.…”
Section: On the Interface Between Sdt And Psimentioning
confidence: 99%
See 2 more Smart Citations
“…We begin with the piece by Koole et al () in part because SDT has had a rich history of connecting with scholars in PSI (e.g., Ryan, Kuhl, & Deci, ), and more generally, the longer tradition of volitional psychologies from Germany (e.g., Heckhausen, ; Krapp & Ryan, ). Recently, Ryan (), in a volume honoring PSI founder Julius Kuhl, suggested that SDT and PSI are “sibling theories,” both being organismic in their meta‐theoretical assumptions, and overlapping in their interests in autonomy and control in human behavior.…”
Section: On the Interface Between Sdt And Psimentioning
confidence: 99%
“…Koole et al () highlight the evidence base of PSI which has shown how its personality dimensions of action orientation and state orientation , typically measured with self‐report, predict differences in engagement, coping, and wellness, especially under challenging conditions. They also provide their own review of SDT, much of with which we can concur.…”
Section: On the Interface Between Sdt And Psimentioning
confidence: 99%
See 1 more Smart Citation
“…Both classic and modern psychoanalytic and humanistic theories have suggested that incongruence between conscious and unconscious emotional responses lead to mental illness (Shedler, ) and stunt personal growth (Koole, Schlinkert, Maldei, & Baumann, ). Consistent with these ideas, well‐being is lower and psychological symptoms are increased among people with greater incongruencies between implicit and explicit motivation (Baumann, Kaschel, & Kuhl, ) or implicit and explicit self‐esteem (Phillips & Hine, ).…”
Section: Introductionmentioning
confidence: 99%
“…Both classic and modern psychoanalytic and humanistic theories have suggested that incongruence between conscious and unconscious emotional responses lead to mental illness (Shedler, 2010) and stunt personal growth (Koole, Schlinkert, Maldei, & Baumann, 2018).…”
mentioning
confidence: 99%